2006
DOI: 10.1103/physreve.73.021703
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of phase separation of polymer–liquid-crystal mixtures and the effect of confining external surfaces

Abstract: A Monte Carlo simulation is performed on a lattice model of a binary mixture of nematogenic liquids and polymers to study the main aspects of phase separation including the influence of external surfaces. The system was investigated at various temperatures, concentrations, and degrees of polymerization. The results seem to fit well within Flory-Huggins theory predictions. It is also shown that in some cases the anisotropy plays an important role in structure formation. The influence of the external surfaces on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Evidently, if the surface segregation is not incorporated, the dynamic morphologies of alloy melt show a transition from disperse microstructure into bicontinuous microstructure with the increase of the fluidity parameter. Bažec and Žumer [9] found that the surface effect has a great influence on phase separation. In our model, the surface free energy is logically considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, if the surface segregation is not incorporated, the dynamic morphologies of alloy melt show a transition from disperse microstructure into bicontinuous microstructure with the increase of the fluidity parameter. Bažec and Žumer [9] found that the surface effect has a great influence on phase separation. In our model, the surface free energy is logically considered.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, theoretical investigation of phase separation mainly focuses on high molecular weight polymers [8,9] , water [10] , water-oil-surfactants [11] , bilayer lipid membranes [12] and lysozymes [13] . Experimental studies [2,14,15] on phase separation extend to ternary alloys, which mainly explores the phase separation mechanism by analyzing solidified microstructures.…”
mentioning
confidence: 99%
“…To investigate the behaviour of the mixture in the bulk, the separation correlation length [22,23] ξ m and ξ lc were evaluated. According to [22], Γ(R) denotes the correlation function such that…”
Section: Lc-polymer Mixture: Influence Of the Degree Of Polymerizationmentioning
confidence: 99%
“…Bažec and Žumer107 performed an MC simulation on a lattice model of a binary mixture of nematogenic liquids and polymers to study the main aspects of phase separation including the influence of external surfaces. During the time of thermalization, the polymer bonds were fixed.…”
Section: Simulation Studies Of Pdlcs (Previous and Current Studies)mentioning
confidence: 99%